Mechanism of phase structure modulating damping in Fe73Ga27 alloy. (July 2023) - Yan, Shaowen; Mu, Xing; Liu, Bingjie; Xu, Lihong; Qi, Yan; Zhang, Hongping
Abstract: The magnetostriction and damping performance of Fe–Ga alloy are closely related to the phase structure. In this paper, the phase structure of Fe73 Ga27 alloy was regulated by homogenization + aging treatment. The results show that the Fe73 Ga27 alloy with modified-D03 phase has higher damping performance at lower amplitudes, and the damping peak is nearly 1.3 times that of only solution-treated alloy. The modified-D03 phase with tetragonal structure leads to local tetragonal distortion of the matrix, which enhances the magnetostriction and magneto-mechanical damping. In addition, the presence of the modified-D03 phase also increases the sensitivity of the alloy to stress. The Fe73 Ga27 alloy with L12 phase as the main phase has higher damping performance at higher amplitudes. When the amplitude is higher than 3 × 10 −4, the damping value is more than 1.6 times that of only solution-treated alloy. The mismatch between the L12 phase and matrix with body-centered cubic structure greatly improves the nonmagnetic damping. The strain mismatch between the L12 phase and the matrix causes interfacial sliding under load to provide interfacial damping. The high-density dislocation due to the thermal mismatch effect enhances dislocation damping. Highlights: Enhanced magneto-mechanical damping by obtaining tetragonal modified-D03 phase. L12 phase provides high damping due to interface and dislocation damping. Interface damping due to strain mismatch between L12 phase and matrix. Dense dislocations generated by thermal mismatch enhance dislocation damping.